2010
DOI: 10.1038/aps.2010.96
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like factor 4 interacts with p300 to activate mitofusin 2 gene expression induced by all-trans retinoic acid in VSMCs

Abstract: Aim: To elucidate how krüppel-like factor 4 (KLF4) activates mitofusin 2 (mfn-2) expression in all-trans retinoic acid (ATRA)-induced vascular smooth muscle cell (VSMC) differentiation. Methods: The mfn-2 promoter-reporter constructs and the KLF4 acetylation-deficient or phosphorylation-deficient mutants were constructed. Adenoviral vector of KLF4-mediated overexpression and Western blot analysis were used to determine the effect of KLF4 on mfn-2 expression. The luciferase assay and chromatin immunoprecipitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Recently, we published that KLF15 is a critical transcriptional regulator of podocyte differentiation (21). Furthermore, KLF4 was found to play a critical role in regulating mitochondrial fusion proteins in vascular smooth muscle differentiation (22). In addition, paralogs of KLF1 (specificity proteins) have been shown to transcriptionally regulate cytochrome c subunit genes in primary neurons (23).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we published that KLF15 is a critical transcriptional regulator of podocyte differentiation (21). Furthermore, KLF4 was found to play a critical role in regulating mitochondrial fusion proteins in vascular smooth muscle differentiation (22). In addition, paralogs of KLF1 (specificity proteins) have been shown to transcriptionally regulate cytochrome c subunit genes in primary neurons (23).…”
Section: Discussionmentioning
confidence: 99%
“…These data support a cell-type specific regulation of KLF4 expression, and potentially function. Although MAPK, Pi3K and NF-κB have been mentioned to be important in KLF4 expression or function in different cell types (42)(43)(44)(45), the pneumococci-related KLF4 expression was strictly independent of the Pi3K and MAPK signaling pathways or NF-κB activation. The non-receptor protein tyrosine kinase family src includes nine members: src, yes, fyn, lck, hck, blk, lyn, fgr.and frk (46).…”
Section: Discussionmentioning
confidence: 99%
“…Expression-Previous studies showed that in VSMCs ATRA induces KLF4 expression and its post-translational modifications, including phosphorylation and acetylation (15,16,35). However, the underlying mechanism by which ATRA regulates Klf4 transcription in VSMCs remains largely unknown.…”
Section: Rar␣-mediated Atra-induced Klf4mentioning
confidence: 99%